Angiotensin-converting enzyme insertion/deletion polymorphism in hypertrophic cardiomyopathy: An Egyptian case control study - Kassem, Heba Sh; Algendy, Sherif A.; Azer, Remon S.; Moharem, Sarah; Ayad, Maha S.; Magdy, Gehan; Elguindy, Ahmed; Yacoub, Magdi H. (The Egyptian heart journal, 2014)
Hypertrophic Cardiomyopathy (HCM) is a disease characterized by genetic and phenotypic heterogeneity. Renin–angiotensin–aldosteron be system (RAAS) is a potential disease modifier. The aim of the present case control study is evaluation of the controversial role of ACE I/D polymorphism in HCM among Egyptians. The study comprised 211 unrelated HCM patients (138 sporadic, 73 familial) and 203 age and sex matched ECG screened healthy volunteers. ACE I/D polymorphism was determined using previously described PCR and gel electrophoresis based method. Distribution of ACE genotype among the Egyptian controls was in Hardy-Weinberg equilibrium (P=0.778) but not in HCM patients (P=0.0010). The ACE DD genotype was significantly higher among HCM patients (P=0.049), particularly in sporadic HCM group compared with familial cases (P=0.0001). In addition, the distribution of D allele was significantly higher in HCM patients carrying sarcomeric mutations in TNNT2 and MYH7, (P=0.0476). There was no observed significant effect of the ACE genotypes on the phenotypic expression of the disease. The finding of higher frequency of DD genotype among HCM patients compared to healthy volunteers, particularly so, in sporadic cases suggests that HCM expression is possibly influenced by a genetically predisposed milieu partially determined by the ACE I/D variants. Despite the lack of significant correlation between I/D variants and clinicopathologic characteristics of the HCM patients, however, the higher prevalence of D allele among TNNT2 and MYH7 mutation carriers may contribute to the variable disease outcome among sarcomeric gene positive cases, such a correlation can only be proven through long term follow up studies.